Addressing Diversity in PTSD Treatment: Clinical Considerations and Guidance for the Treatment of PTSD in LGBTQ Populations - Livingston, Nicholas A. (Curr Treat Options Psychiatry, 2020)
PURPOSE OF REVIEW: Trauma exposure is widespread but is especially common among lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals. LGBTQ individuals also experience higher rates of discrimination, victimization, and minority stress which can complicate posttraumatic stress disorder (PTSD) treatment but also represent independent intervention targets. In this review, we highlight existing evidence-based practices, current limitations, and provide recommendations for care in the absence of established guidelines for treatment PTSD among LGBTQ patients. RECENT FINDINGS: Trauma-focused therapies (e.g., CPT, PE) and medications (e.g., SSRIs, SNRIs) have shown benefit for people with PTSD. However, evaluations of these interventions have failed to examine the role of LGBTQ identities in recovery from trauma, and existing PTSD treatments do not account for ongoing threat to safety or the pervasive minority stress experienced by LGBTQ patients. In addition, many LGBTQ patients report negative experiences with healthcare, necessitating increased education and cultural awareness on the part of clinicians to provide patient-centered care and, potentially, corrective mental health treatment experiences. SUMMARY: Providers should routinely assess trauma exposure, PTSD, and minority stress among LGBTQ patients. We provide assessment and screening recommendations, outline current evidence-based treatments, and suggest strategies for integrating existing treatments to treat PTSD among LGBTQ patients.